Morphological Patterns of Urban Blocks in the City of Patos, Paraíba, Brazil - Castro, Alexandre Augusto Bezerra da Cunha; Albuquerque, Sheila Rodrigues de; Silveira, Krisliane Kellen Lima; Silva, Guilherme Honório da; Gonçalves, Ashiley Pereira (Technical and Scientific Journal Green Cities, 2024)
The block represents one of the main structuring elements of urban form, serving as a point of connection between public and private spaces. In various approaches and morphological concepts, the block is identified as a fundamental component and can be analysed at different scales, from the city to the building, considering its architectural typology. This article aims to investigate the morphological patterns of blocks in the city of Patos, Paraíba, Brazil. The research problem is centred on the discussion of the types of blocks that have been built in the process of evolution and occupation of urban space. The methodology consists of modelling georeferenced data on morphological elements and calculating the length and connectivity of block segments, area, compactness and occupancy rate of blocks. The findings indicate a morphological pattern of the blocks associated with the centre-periphery dichotomy: the central area of the city has a higher building density, smaller and more compact blocks, with a greater human scale and public-private interface, while the more peripheral zones have smaller, less compact and dispersed blocks, generating more sprawling areas with less direct relationship between public and private spaces. These results help us to better understand how the process of urban evolution has moulded the city's blocks, associating them with different socio-spatial phenomena.
Keywords: Urban Block; Urban morphology; Urban Evolution